2020
DOI: 10.1080/14616696.2020.1818270
|View full text |Cite
|
Sign up to set email alerts
|

On solidarity and volunteering during the COVID-19 crisis in Denmark: the impact of social networks and social media groups on the distribution of support

Abstract: This paper unfolds how informal civil society quickly mobilised citizen-to-citizen support when government and non-government organisations locked down during the COVID-19 pandemic. The paper focuses on two elements of the mobilisation: the role of social networks and social media groups. It reveals that the vast majority of this support was distributed through existing social networks and, therefore, not available to those lacking social connections. However, we also find that social media groups played an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 24 publications
0
84
0
10
Order By: Relevance
“…Previous research has suggested that misinformation from media usage, particularly social media usage through Facebook or Twitter, can be more harmful to one's mental health (Allington et al 2020;Limaye et al 2020;Ni et al 2020). Whilst other evidence suggest social media may be beneficial in creating social support during this pandemic; however, this is only applicable for those who have access to these resources (Carlsen et al 2020;Saud et al 2020). Based off World Health Organization (2020) guidelines, while socialising over media platforms such as Facetime and Whatsapp can be useful for social support, it is important not to spend a significant portion of the day checking and scanning media platforms for information.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that misinformation from media usage, particularly social media usage through Facebook or Twitter, can be more harmful to one's mental health (Allington et al 2020;Limaye et al 2020;Ni et al 2020). Whilst other evidence suggest social media may be beneficial in creating social support during this pandemic; however, this is only applicable for those who have access to these resources (Carlsen et al 2020;Saud et al 2020). Based off World Health Organization (2020) guidelines, while socialising over media platforms such as Facetime and Whatsapp can be useful for social support, it is important not to spend a significant portion of the day checking and scanning media platforms for information.…”
Section: Discussionmentioning
confidence: 99%
“…While, on the one hand, crises tend to exacerbate negative conditions, inequalities, and competition between groups for scarce resources, they can also often inspire individuals and social groups to engage in remarkable acts of solidarity, mutual support and help, even in difficult conditions (Grasso and Giugni 2019; Koos 2019). Some papers in this special issue demonstrated the multiple ways in which people may look after each other, positively relying on social networks (Carlsen et al 2020), and mobilizing people in favor of migrants (Zajak et al 2020). One study from Italy (Moralli and Allegrini 2020) further discussed the potential for social innovation triggered by the pandemic when focusing on the mobilization of resources by people living in vulnerable areas.…”
Section: Solidarity and Cohesionmentioning
confidence: 99%
“…While acts of solidarity stood out in the 'heydays' of the first lockdown (e.g. the Czech altruistic wave of home-made production of face masks (Trnka 2020)) at least in some countries (Carlsen et al 2020), overall levels of social cohesion may have palpably declined, especially among the most deprived communities (Borkowska and Laurence 2020). Thus, we need to better understand how acts of solidarity and social cohesion are connected, and how patterns might differ across countries and communities.…”
Section: Solidaritymentioning
confidence: 99%
“…To be sure, ICT has long been on the radar of third sector scholars, and studies abound on how many-to-many communication enables new ways of connecting, mobilizing, recruiting, and managing civically engaged people (Amichai-Hamburger, 2008 ; Bennett & Segerberg, 2012 ; Bernholz, 2017 ; Brainard & Brinkerhoff, 2004 ; Eimhjellen, 2019 ; Piatak et al 2019 ). The phenomenon of virtual volunteering, however, is more recent (Ihm, 2017 ), and while the COVID-19 pandemic triggered a host of virtual volunteering initiatives (Carlsen, Toubøl, and Brincker 2020 ), the field of online volunteer research remains in its infancy (Eimhjellen, 2019 ). At present, the literature is dominated by descriptive and exploratory studies that demarcate and map the field (Ackermann and Manatschal 2018 ; Mukherjee, 2011 ), supply advice to managers of virtual volunteers (Cravens, 2000 ; Dhebar & Stokes, 2008 ), or map the motivations and characteristics of volunteers (Eimhjellen, 2019 ).…”
Section: The Pursuit Of Intimacy and The Production Of Inequality In mentioning
confidence: 99%